Area-dependent gain and noise characteristics of mid-wavelength infrared HgCdTe planar electron avalanche photodiodes. (1st August 2022) - Yang, Dan; Guo, Huijun; Zhu, Liqi; Yang, Liao; Chen, Lu; Lin, Chun; Ding, Ruijun; He, Li
Abstract: This paper mainly investigates the area-dependent gain and noise characteristics of mid-wavelength infrared (MWIR) Hg0.7 Cd0.3 Te planarelectron avalanche photodiodes (e-APDs) operated at 80 K. The 10- μ m-radius diode exhibits low dark current in the magnitude of 10 –13 A below −5.5 V, high gain up to 1270 at −10 V, and low excess noise factor between 1 and 1.2. The optimal performances are compromised by tunneling current, which should be further suppressed. Studies on variable-area diodes show that larger diodes have a reduced gain due to a smaller contribution from edge gain, as well as an increased 1/ f noise and corner frequency due to higher defect density. From the gain and noise perspectives, HgCdTe e-APDs with smaller junction areas are more suitable for focal plane array (FPA) applications.